Inventari del tresor litúrgic de l'altar de Sant Pere de la Catedral de Vic de principi del segle XIII - Sanjosé i Llongueras, Lourdes de (Miscel·lània litúrgica catalana, 2016)
The author presents the unpublished inventory of liturgical objects of Saint Peters altar in Vic Cathedral, possibly dating to the early 13th century. The inventory can be found in folio 152 of Liber dotationum antiquarum (ACV). This article analyzes the wills and the figures of Pere de Tavertet (1157-1218), sacristan, and Guillem de Tavertet, his nephew and bishop of Vic from 1195 to 1233. The author provides a study of the pieces included in the inventory, the most important of which is the magnum chalice which Pere de Tavertet bequeathed to the altar.